2003
DOI: 10.1097/01.ccm.0000063579.43470.aa
|View full text |Cite
|
Sign up to set email alerts
|

Depressed interleukin-12-producing activity by monocytes correlates with adverse clinical course and a shift toward Th2-type lymphocyte pattern in severely injured male trauma patients

Abstract: Major trauma results in an early and marked decrease in monocyte cytokine-producing activity. The trauma-induced depression in IL-12 production by the mononuclear phagocyte system may promote T-cell commitment toward a Th2 pattern early after trauma. The appearance of the Th2 pattern is the result of elevated numbers of IL-4-producing cells without major alterations in T-cell interferon-gamma-producing capacity. The degree of alterations in monocyte and T-cell responses on day 2 postinjury correlates with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 45 publications
9
84
1
2
Order By: Relevance
“…This suggests that the clinical worsening of septic patients is often induced and maintained by the specific shift towards a predominant Th2 phenotype. This result is in agreement with previous published data indicating a lower Th1/Th2 ratio of cytokine-producing T cells (or an increased IL-4-producing CD4+ T cells) in PBMC of septic or polytraumatic patients [8,17]. On the other hand, it has been shown that in the murine model of sepsis obtained with the cecal ligation and puncture, the release of IL-4 was markedly increased and the IL-4-induced activation of the STAT6 pathway contributed to the immunosuppression and death in sepsis [26].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This suggests that the clinical worsening of septic patients is often induced and maintained by the specific shift towards a predominant Th2 phenotype. This result is in agreement with previous published data indicating a lower Th1/Th2 ratio of cytokine-producing T cells (or an increased IL-4-producing CD4+ T cells) in PBMC of septic or polytraumatic patients [8,17]. On the other hand, it has been shown that in the murine model of sepsis obtained with the cecal ligation and puncture, the release of IL-4 was markedly increased and the IL-4-induced activation of the STAT6 pathway contributed to the immunosuppression and death in sepsis [26].…”
Section: Discussionsupporting
confidence: 83%
“…There is a general consensus that initial immune response in sepsis is characterized by the hyper-expression of proinflammatory mediators, even though it may rapidly progress to a state of hypoinflammation prevalently due to the downregulation of the major protective mechanisms. Indeed a shift to a less protective T (namely Th2 cells) cells secreting anti-inflammatory cytokines have been described to be relevant for a poor prognosis [7,17]. Even though timing of these alterations are not fixed and the involved mechanisms may be different in each patient, however measurement of circulating inflammatory mediators may prove to be useful in evaluating the stage of sepsis and in adopting the most appropriate treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…MHC II expression on splenic and peritoneal macrophages was also determined using flow cytometry (39). Macrophages were identified using PE-labeled anti-mouse F4/80 Abs (eBioscience).…”
Section: Flow Cytometry Determinations For Detection Of Thymocyte Apomentioning
confidence: 99%
“…However, high doses of LPS can result in suppressed extracellular signal-regulated kinase activity during subsequent secondary LPS exposures, including mitogen-activated protein kinases (MAPKs) and c-Jun NH 2 -terminal kinase (JNK), with subsequent decreases in NF-κB and AP-1 transcription factor activity (Adib-Conquy et al, 2000;Fan & Cook, 2004;West et al, 2007). This decrease in TLR4-mediated signal transduction can lead to decreased production of proinflammatory genes such as Tumor Necrosis Factor-alpha (TNFα), interleukin(IL)-1 and IL-12, among others (Munoz et al, 1991;Spolarics et al, 2003). Prolonged exposure to microbial products (and LPS in particular) also has a deleterious effect on the proinflammatory responses of neutrophils, although this response is distinct from the phenotype of "LPS tolerized" macrophages.…”
Section: Immune Cell Dysfunction During Sirsmentioning
confidence: 99%